Classification of sustainability potential of genetic resources of local grapevine varieties in Serbia - Jakšić Darko D.; Perović Veljko S.; Nikolić Dragan T.; Ivanišević Dragoslav M.; Ćirković Bratislav M.; Stojanović Vojkan D.; Bradić Ivan Z. (Zbornik Matice Srpske za Prirodne Nauke, 2024)
The starting point for every viticultural and wine-producing country with respect to local grapevine varieties is their identification, inventory, preservation and development of genetic resources of those varieties. There are currently 224 grapevine varieties cultivated in Serbia for the purpose of commercial production of grapes and wine. Out of that number, 31 wine varieties are local. Vineyards under those varieties can be differentiated by their importance for production of grapes and wine, and by the level of their endangerment, that is, sustainability in conditions caused by climate changes. This paper presents the creation, that is, the modeling of the Method for Vineyard Sustainability Claswine grapevine varieties on grounds of their endangerment and sustainability, based on 20 examined and categorized individual vineyard sustainability parameters; to carry out comsification (MVSC). The purpose of MVSC classification is: to valorize vineyards with local prehensive classification into one of the four established vineyard sustainability classes (Class A - very endangered vineyards, Class B - endangered vineyards, Class C - sustainable vineyards and Class D - very sustainable vineyards); spatial identification and presentation of vineyards based on determined vineyard sustainability class through application of GIS technology; and finally, application of Network Analysis (NA), prioritization of examined parameters and, therefore, vineyards. A total of 10,402 vineyards under local grapevine wine varieties were used for modeling, and it was determined that 29 vineyards with the total surface of 1.2 hectares should be classified in Class A, while 2,883 vineyards with the total surface of 158.2 hectares should be classified in Class B. With respect to the strength of 20 individual vineyard sustainability parameters, it was determined that the parameter Structure of the vine rootstock (SVR) has the greatest impact, and priority in selection of vineyards in different sustainability classes should be given to vineyards without rootstocks. In accordance with the scientific justification of obtained results, the MVSC enables comprehensive classification of the potential for sustainability of genetic resources of local grapevine varieties in Serbia, and it can be applied in other countries and wine-growing areas, as well as to other groups of grapevine varieties.